2008
DOI: 10.1177/1043659608322418
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Screening in Canadian First Nation Cree Women

Abstract: Challenges faced by First Nation Cree women when contemplating cervical screening are presented. Nursing sensitivity is needed to strategize access to cervical screening that is culturally appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 15 publications
2
45
1
4
Order By: Relevance
“…We found that Inuit women had a strong preference for having cervical cancer screening performed by female health practitioners and that they wanted explanations to be given to them throughout the Pap smear examination. These preferences were also shown among Aboriginal populations in Canada and the United States (17,25). When planning health services these concepts should be kept in mind, as Coe et al (16) found that Pap smear adherence was lower among women who reported that they would refuse a male provider.…”
Section: Discussionmentioning
confidence: 68%
“…We found that Inuit women had a strong preference for having cervical cancer screening performed by female health practitioners and that they wanted explanations to be given to them throughout the Pap smear examination. These preferences were also shown among Aboriginal populations in Canada and the United States (17,25). When planning health services these concepts should be kept in mind, as Coe et al (16) found that Pap smear adherence was lower among women who reported that they would refuse a male provider.…”
Section: Discussionmentioning
confidence: 68%
“…Having to wait for results prolonged anxiety until the ‘all clear’ was given . Other factors that enhanced anxiety about cancer were recalls, only being contacted if further tests were needed (which created prolonged anxiety about having missed the call), and unclear communication of results including benign findings, which put some people off reattending screening, sometimes permanently: ‘The doctor [said] oh it's just calcium deposits—which took 30 years off my life’ . Thus, some people use screening to reduce cancer fear, but the screening test itself is also fear provoking.…”
Section: How Do I Keep the Enemy At Bay?mentioning
confidence: 99%
“…Most screening studies intended to increase cancer screening rates focus on specific vulnerable and marginalized populations known to have low cancer screening rates [2-10], such as: immigrants [11-17], ethnic minorities [2,11,15,18,19], underserved populations [20,21], uninsured [11,18,20], individuals with mental health issues [22-24], indigenous populations [4,15,25,26] and rural residents [15,27,28]. These vulnerable and marginalized populations tend to be localized geographically, resulting in community or neighbourhood level studies designed to inform changes at the local level and to be generalizable to other vulnerable and marginalized populations in other geographic locations.…”
Section: Introductionmentioning
confidence: 99%